Mechanics of composite and multi-functional materials. Volume 7 : proceedings of the 2016 Annual Conference on Experimental and Applied Mechanics - Ralph, W. Carter; Singh, Raman; Tandon, Gyaneshwar; Thakre, Piyush R.; Zavattieri, Pablo; Zhu, Yong (Springer, 2016)
Mechanics of Composite, Hybrid, and Multifunctional Materials, Volume 7 of the Proceedings of the 2016 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the seventh volume of ten from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on a wide range of areas, including: Recycled-Constituent Composites Nano and Particulate Composites Damage Detection and Non-Destructive Evaluation of Composites Fracture and Fatigue Novel Developments in Composites Additive Manufacturing of Composites Mechanics of Graphene & Graphene Oxide Smart Materials Novel Developments in Composites Manufacturing and Joining of Composites.
Keywords: Composite materials -- Mechanical properties -- Congresses.; elektronické knihy; electronic books